ANALISA KESALAHAN BERBAHASA DALAM PENGGUNAAN KALIMAT MELALUI MEDIA KOMIK - Hertiki, Hertiki (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Media komik saat ini sudah sangat populer di kalangan mahasiswa. Penelitian ini fokus pada penggunaan ketrampilan menulis dalam bentuk komik, terutama bagi pemelajar BIPA yaitu pemelajar asal Vietnam. Desain dalam penelitian ini adalah kualitatif. Kesimpulan dari penelitian ini adalah komik dapat dijadikan sebagai media pendidikan yang membantu para pemelajar BIPA Vietnam terutama dalam keterampilan menulis untuk belajar lebih efektif lagi. Bukan hanya karena komik sebagai salah satu media pembelajaran, tetapi komik sudah dikenal baik oleh para pemelajar BIPA di Vietnam. Untuk mencapai peningkatan hasil belajar bahasa Indonesia terutama dalam ketrampilan menulis, penggunaan media komik dianggap lebih efektif karena dikemas dengan cara menarik yaitu dengan menggunakan gambar dan kata-kata yang mendukung. Kata kunci: kesalahan berbahasa, penggunaan kalimat, komik Abstract Comics are well-known among students in Ho Chi Minh City, Vietnam. This paper aims to discuss and explore the usage of a comic book to construct sentences in the Indonesian language lessons for BIPA (learners in University of Social Sciencs and Humanities). A qualitative method is designed in this research for the outcomes. From 17 students who joined the BIPA class, there were thirteen students (70%) who stated that Cartoon Story Maker is very interactive to be used in the teaching learning Indonesian language in the class. Another difficulty that they face is mostly the use of Indonesian language (47.4 %), such as: spelling and lack of vocabulary in making sentences and conversations. It took approximately 2-3 hours to create a story using Cartoon Story Maker. Comics can generate ideas for BIPA students in Vietnam in learning the Indonesian language in a fun and effective manner, especially in writing skills. Since a comic book is full of illustrations, it enhances the undergraduate students’ understanding immediately and they are able to produce sentences with minimal help from the lecturer. Therefore, it is hoped that comics can be an edutainment tool in promoting writing in the classroom. Keywords: language error, usage of sentences, comics